A review on tribological wear test rigs for various applications - Nirmal, Umar; Albawab, Tarek Mhd Moataz; Halim, Isa; Ahmed Salem, Mohammed; Elsayed, Mahmoud; Singh, Jasspeed (Penerbit UTHM, 2018)
To mimic a tribosystem setup to the real time model while taking into consideration the subject of green tribology, many tribological wear test rigs are invented.The current work is a dedicated review on the latest development of various tribological wear test rigs build for numerous applications.With the aid of diagrams,the working principles of the machines which are built on specific standards are discussed.Their operating parameters associated with related research using these machines are also included.In addition,recommendations and directions for improvements in tribology machines are reported.